IMPLEMENTASI MANAJEMEN PENDIDIKAN BERBASIS MASYARAKAT DALAM PROSES RESILIENSI ORGANISASI DI MADRASAH DINIYAH ITTIHADUL MUBALLIGHIN KOTA MALANG - Iim Muzayyanah; Abdul Malik Karim Amrullah; Mokhammad Yahya (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to describe the implementation of Community-Based Education Management (CBEM) and analyze its impact on organizational resilience at Madrasah Diniyah Ittihadul Muballighin, Malang City. CBEM is a managerial approach emphasizing institutional autonomy and community participation. This research employed a qualitative case study method, with data collected through observation, in-depth interviews, and documentation. The findings revealed: (1) the reactivation of the madrasah was driven by community awareness of religious education needs; (2) the institution is managed autonomously using local resources; (3) relationships with stakeholders enhance the institution's adaptive capacity; and (4) the curriculum is contextualized to the community's characteristics. These findings suggest that CBEM contributes significantly to the resilience of non-formal educational institutions.